Antimicrobial consumption surveillance in Uganda: Results from an analysis of national import data for the human health sector, 2018–2021 - Marion Murungi; Helen Byomire Ndagije; Reuben Kiggundu; Diana Nakitto Kesi; JP Waswa; Kalidi Rajab; Mark Barigye; Allan Serwanga; Leonard Manirakiza; Hassan Kasujja; Ddembe Kaweesi; Mohan P. Joshi; et al. (Journal of Infection and Public Health, 2023)
Background: The surveillance of antimicrobial consumption (AMC) is critical to developing appropriate antimicrobial stewardship interventions. It is a key component of World Health Organization’s (WHO) Global Action Plan on Antimicrobial Resistance and the Uganda Antimicrobial Resistance National Action Plan 2018–2023. Our study’s objective was to determine the national consumption of all antimicrobials. Methods: Data on all imported antimicrobials were retrieved from paper-based records and entered in the web-based National Drug Authority (NDA) management information system from 2021. The import data for the year is a proxy for nationwide consumption because they account for 95% of all medical products. The NDA authorizes all imports to the country regardless of final distribution in the supply chain. The data were analyzed in accordance with WHO Anatomical Therapeutic Chemical codes and defined daily dose (DDD) methodology. We also retrieved consumption data for 2018, 2019, and 2020 that were previously submitted by Uganda to WHO’s Global Antimicrobial Resistance and Use Surveillance System. Results: In 2021, the average DDD per 1000 inhabitants was 29.02 for all antimicrobials; 80.7% of antimicrobials consumed were oral. Penicillins (27.6%) were the most consumed antimicrobial class, followed by sulfonamides and trimethoprim (15.5%). Based on WHO’s Access, Watch, and Reserve (AWaRe) antibiotic classification, 62.91% of AMC was from the access class, with watch class averaging 14.51% in the period 2018–2021. Watch class AMC spiked in 2021 (34.2%) during COVID-19 pandemic compared to 2020 (24.29%). Azithromycin and ciprofloxacin were the most consumed watch class antimicrobials in 2021. Conclusions: The relatively high consumption of injectable antimicrobials and year over year increase in watch class AMC requires urgent stewardship interventions. Further work is needed to establish a system for longitudinal AMC surveillance that is well resourced and funded to overcome the challenges of estimation and provide more accurate data on consumption and use patterns.